2016
DOI: 10.1016/j.cmet.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The Chromatin Remodeling Complex Chd4/NuRD Controls Striated Muscle Identity and Metabolic Homeostasis

Abstract: Heart muscle maintains blood circulation, while skeletal muscle powers skeletal movement. Despite having similar myofibrilar sarcomeric structures, these striated muscles differentially express specific sarcomere components to meet their distinct contractile requirements. The mechanism responsible is still unclear. We show here that preservation of the identity of the two striated muscle types depends on epigenetic repression of the alternate lineage gene program by the chromatin remodeling complex Chd4/NuRD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 44 publications
2
75
0
Order By: Relevance
“…NuRD is highly conserved amongst metazoans and has been shown to play important roles in cell fate decisions in a wide array of systems (Denslow & Wade, ; Signolet & Hendrich, ). For example, in embryonic stem (ES) cells, NuRD controls nucleosome positioning at regulatory sequences to finely tune gene expression (Reynolds et al , ; Bornelöv et al , ), and in somatic lineages, NuRD activity has been shown to prevent inappropriate expression of lineage‐specific genes to ensure fidelity of somatic lineage decisions (Denner & Rauchman, ; Knock et al , ; Gomez‐Del Arco et al , ; Loughran et al , ). It was recently demonstrated that this is achieved in both ES cells and B‐cell progenitors by restricting access of transcription factors to regulatory sequences (Liang et al , ; Loughran et al , ; Bornelöv et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…NuRD is highly conserved amongst metazoans and has been shown to play important roles in cell fate decisions in a wide array of systems (Denslow & Wade, ; Signolet & Hendrich, ). For example, in embryonic stem (ES) cells, NuRD controls nucleosome positioning at regulatory sequences to finely tune gene expression (Reynolds et al , ; Bornelöv et al , ), and in somatic lineages, NuRD activity has been shown to prevent inappropriate expression of lineage‐specific genes to ensure fidelity of somatic lineage decisions (Denner & Rauchman, ; Knock et al , ; Gomez‐Del Arco et al , ; Loughran et al , ). It was recently demonstrated that this is achieved in both ES cells and B‐cell progenitors by restricting access of transcription factors to regulatory sequences (Liang et al , ; Loughran et al , ; Bornelöv et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the increased expression after insulin treatment could possibly impact development. CHD4 , which represents the main component of the nucleosome remodeling and the deacetylase complex that is involved in epigenetic transcriptional repression (Gomez‐Del Arco et al, ; Singh et al, ), was hypomethylated and upregulated in both insulin‐treated groups. The HIST1H1C gene encodes a histone H1 subtype that is involved in the dynamics of the chromatin structure (Clausell, Happel, Hale, Doenecke, & Beato, ) and has a function in organizing the epigenetic landscape (Sadakierska‐Chudy, Kostrzewa, & Filip, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the role of cytokine/chemokine signaling and integrins/extracellular matrix, as identified in our pathway analysis of the transcriptome data, remains to be determined. Nevertheless, the current study adds to a growing list of epigenetic factors that regulate heart physiology such as the PRC2 polycomb complex and the NuRD chromatin-remodeling complex [3841]. …”
Section: Discussionmentioning
confidence: 99%